2021
DOI: 10.37527/2021.71.2.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparación de las Guías Alimentarias en nueve países de las Américas

Abstract: Las Guías Alimentarias Basadas en Alimentos (GABA) son un instrumento nacional de educación nutricional destinadas a la población general. En el contexto de alta prevalencia de enfermedades crónicas no transmisibles, relacionadas con dietas inadecuadas, buscan contribuir a alcanzar mejores estándares de alimentación. En el contexto americano, de alta prevalencia de sobrepeso y obesidad, las GABA forman parte de un conjunto de políticas gubernamentales para combatir estos problemas. El objetivo de este ensayo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Of the 32 countries in Latin America and the Caribbean, less than half had available food guidelines with specific guidance for children under two years old. This tendency toward a less significant quantity has been previously noted in other systematic reviews and continues to be observed in this research [ 1 , 36 , 37 ]. Despite the increasing discussion on the importance of developing food guidelines, there is a notable need for greater encouragement in developing these documents to reach a larger population of infants and their caregivers [ 5 , 11 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Of the 32 countries in Latin America and the Caribbean, less than half had available food guidelines with specific guidance for children under two years old. This tendency toward a less significant quantity has been previously noted in other systematic reviews and continues to be observed in this research [ 1 , 36 , 37 ]. Despite the increasing discussion on the importance of developing food guidelines, there is a notable need for greater encouragement in developing these documents to reach a larger population of infants and their caregivers [ 5 , 11 ].…”
Section: Discussionsupporting
confidence: 89%
“…The Brazilian Population Food Guide stands out for its strong social participation in the guide’s elaboration process, which has been recognized as an important characteristic in other studies that oppose one of the major obstacles to the implementation of food guidelines [ 36 , 37 , 57 ]. Additionally, the Brazilian Guide showed the best evaluation performance due to the extent of its content, allowing for the coverage of more topics such as environmental impacts and social participation, resulting in a higher overall score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation